Stereotypes in the German Physics Olympiad - Hurdle or no Harm at all? - Ladewig, Antonia; Köller, Olaf; Neumann, Knut (Frontiers in Education, 2022)
The German Physics Olympiad is a science competition in which students can compete to measure their Physics knowledge and skills with other students. Female participants are underrepresented and typically drop out of the competition earlier than their male counterparts. As the cause for this underrepresentation, social identity threat theory identifies a threat to women’s gender identity in the predominantly male environment. Stereotype threat theory adds negative stereotypes about women’s abilities in physics as a heightening factor. In this study, growth mindset and values affirmation interventions, as well as a combination of both methods, were integrated into a weekend seminar of Physics content to protect female participants from the harmful influences of stereotype and social identity threat. As female and male students’ sense of belonging and gender identification remained at equal levels, respectively, after the interventions, the results did not show any effects of stereotype threat or social identity threat for the female students. The results suggest that women who are highly interested and talented in physics and have taken first steps to pursue physics and to engage with the physics community beyond mandatory school education are not as susceptible to stereotypes and harmful cues in the environment as might previously have been assumed. Implications for future research and science competitions are discussed.